Surface oceanographic data (TSG) during MARIA S. MERIAN cruise MSM60 - Karstensen, Johannes (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2019)
The data has been compared with CTD data from 5 dbar . This data has not been checked for outliers or noisy data caused by blocked thermosalinograph pumps. Please use with caution.